Wise Use Of Social Media Amongst Students Senior High School - Sa'ban, L.M. Azhar; Ardiansah Putra, Muhammad Rizal; Arwan, La Ode; Aulia; Rano (Community Development Journal, 2025)
Social media provides many conveniences that can be obtained from cellphones and the internet, almost all students as users of technology and information and prove that at this time life cannot be separated from technology and information. Community Service activities are carried out at SMA Negeri 1 Mawasangka Tengah with the aim of sharing knowledge about the wise use of social media among students. Students should learn more about time management and wise use of social media to deal with the positive and negative impacts of social media. Students can find various sources of lesson-related information on social media. They can search for blogs, videos, articles and other sources that will help their understanding. Students can have a deeper understanding of the subject matter they are learning by using social media. Students can also work together with their friends on social media, they can collaborate in groups, hold conversations and exchange ideas. In addition to increasing student participation, this partnership broadens their perspective. Students can utilize social media to learn and grow. However, in using social media, we must remember about the ethics and safety of its use in order to use social media wisely.